GEOCHEMICAL ASSESSMENT OF ORE SAMPLES FROM ARTISANAL MINING SITES IN ZAMFARA STATE, NIGERIA - Narimi, Abubakar Muhammad; Rafiu, A. A.; Alhassan, U. D.; Idris Nda, A. (FUDMA JOURNAL OF SCIENCES, 2025)
This study focuses on the geochemical characterization of mineralized zones within Zamfara and its surrounding regions, located between latitudes 11°00’N–13°00’N and longitudes 5°00’E–7°00’E. The area is geologically underlain by the Migmatite Gneiss Complex and Schist Belts. Several researchers adopted magnetic filtration techniques such as vertical derivatives and analytic signal in order to delineate structures that may host mineralisation and hydrothermal alteration zones of solid minerals in the area. Other techniques adopted in the area include petrographic analysis. Even though, these methods can complement each other, some of the mineralisation and hydrothermal alteration zones are either too dispersed, in sufficient quantities, or of too low grade to be mined profitably and therefore does not economically contains concentration of ore minerals. Geochemical analysis utilizing X-ray fluorescence (XRF) was conducted to assess the elemental composition and concentration of mineral constituents within various alteration zones. The findings revealed significant concentrations of major oxides by weight, including CaO (18.29%), Al₂O₃ (31.13%), SiO (76.0) Fe₂O₃ (81.81%), SO₃ (0.18%), K₂O (25.29%), Mn₂O₃ (1.67%), P₂O₅ (0.91%), MgO (2.56%), Cr₂O₃ (1.28%), and CuO (0.04%) across multiple sampled locations. These compositions suggest zones of hydrothermal alteration and mineral enrichment, with variations in elemental distribution correlating with localized geochemical anomalies. Therefore, unveiling the rich subsurface geologic structures and mineral conduits coupled with identification of manifested minerals at the surface through geochemical method will improve the output capacity of the mining exploration and mitigate abandon mines. This study improved exploration efficiency by reducing investment risks in low-grade or uneconomic sites through understanding...